Developing a problem-based learning (PBL) curriculum for professionalism and scientific integrity training for biomedical graduate students. Issue 10 (25th August 2010) - Jones, Nancy L; Peiffer, Ann M; Lambros, Ann; Guthold, Martin; Johnson, A Daniel; Tytell, Michael; Ronca, April E; Eldridge, J Charles
Abstract : A multidisciplinary faculty committee designed a curriculum to shape biomedical graduate students into researchers with a high commitment to professionalism and social responsibility and to provide students with tools to navigate complex, rapidly evolving academic and societal environments with a strong ethical commitment. The curriculum used problem-based learning (PBL), because it is active and learner-centred and focuses on skill and process development. Two courses were developed: Scientific Professionalism: Scientific Integrity addressed discipline-specific and broad professional norms and obligations for the ethical practice of science and responsible conduct of research (RCR). Scientific Professionalism: Bioethics and Social Responsibility focused on current ethical and bioethical issues within the scientific profession, and implications of research for society. Each small-group session examined case scenarios that included: (1) learning objectives for professional norms and obligations; (2) key ethical issues and philosophies within each topic area; (3) one or more of the RCR instructional areas; and (4) at least one type of moral reflection. Cases emphasised professional standards, obligations and underlying philosophies for the ethical practice of science, competing interests of stakeholders and oversight of science (internal and external). To our knowledge, this is the first use of a longitudinal, multi-semester PBL course to teach scientific integrity and professionalism. Both faculty and students endorsed the active learning approach for these topics, in contrast to a compliance-based approach that emphasises learning rules and regulations.